Identification of regulatory motif for enhancing expression of oil palm (Elaeis guineensis Jacq.) stearoyl-ACP desaturase 1 - Abu Hanifiah, Farah Hanan (2018)
Understanding the regulation of fatty acid biosynthesis is important for genetic improvement of oil traits especially palm oil yield and composition. Stearoyl-ACP desaturase (SAD) plays a central role in regulating the levels of unsaturated fatty acids in plant storage lipid as the fatty acid composition is known to change during fruit maturity. The sequence of the oil palm SAD promoter contains an array of cis-acting regulatory elements such as phytohormone and light responsive regulatory elements and tissue-responsive regulatory elements that interact with transcription factors to regulate or modify the expression of this gene. This study was undertaken to identify or prove the specific regulatory motif that can enhance or suppress the activity of the oil palm SAD1 promoter and its potential role in regulating fatty acid biosynthesis. The SAD1 promoter of 1111 bp in size was isolated using polymerase chain reaction (PCR). A total of six 5’ deletion fragments of the SAD promoter which are 698 bp (D1), 643 bp (D2), 594 bp (D3), 516 bp (D4), 444 bp (D5) and 413 bp (D6) were isolated by PCR and all the deletion fragments including the full promoter sequence were cloned into a pBGWFS7.0 vector containing both the β-glucuronidase (GUS) and green fluorescent protein (GFP) reporter genes. The recombinant plasmids were bombarded into 12 week after anthesis (WAA) oil palm mesocarp tissues and the gene expression in GFP positive tissues were analyzed by transient GUS assay. The results of the quantitative fluorometric GUS assay showed that GUS activity in the D3 deletion construct (-486 to +108) was significantly increased and was higher than that of the full length promoter. In addition, the D2 (-535 to +108) deletion construct was found to direct the least expression of the GUS reporter gene. This observation suggests the presence of negative cis-acting regulatory element(s) in the deleted -535 to -486 (49 bp).Electrophoretic mobility shift assay (EMSA) was done to identify the specific regulatory element responsible for the altered gene expression in the mesocarp tissues. It was found that the 49 bp region bind to the nuclear protein extract from mesocarp and did not bind to the extract from leaves. Further fine-tuned analysis of this 49 bp region by EMSA using truncated DNA and nucleotide mutations led to the identification of GCTTCA as a novel motif in the SAD promoter. The presence of another known motif LECPLEACS2 (TAAAT) are required for effective competition by GCTTCA in binding to mesocarp nuclear protein extract. GCTTCA with one variant nucleotide is also found in another oil palm fatty acid biosynthetic gene, acylcarrier protein (ACP3) suggesting its potential role in regulating expression in the mesocarp tissues.